The relationship between social anxiety and self-injury of junior high school students: Mediation by intolerance of uncertainty and moderation by self-esteem - Yao, Zhendong; Pang, Lu; Xie, Jin; Shi, Seqin; Ouyang, Min (Frontiers in Public Health, 2023)
The problem of adolescents' self-injury has gradually attracted social attention, however, a lack of research exists on the internal mechanism between social anxiety and self-injury. This study explored the relationship between social anxiety and self-injury in Chinese junior high school students. An adolescent self-injury questionnaire, social anxiety scale, intolerance of uncertainty questionnaire and self-injury questionnaire were used to survey 614 junior high school students. The results showed that: 1) social anxiety had a significant positive predictive effect on self-injury; 2) intolerance of uncertainty had a significant mediating effect between social anxiety and self-injury; and 3) self-esteem had a significant moderating effect on the mediating effect of intolerance of uncertainty. The study suggested that social anxiety in junior high school students has an impact on self-injury through mediation of intolerance of uncertainty and modulation of self-esteem.